The Mother of Islamic Sciences in Al-Ghazali's Perspective - Sabil, Jabbar (Jurusan Aqidah dan Filsafat Islam Universitas Negri Sunan Gunung Djati Bandung, 2024)
Al-Ghazali stated that Kalam is the foundation (mabadi) of Islamic sciences. Does it mean the mother of Islamic sciences? It must be clarified because it is the basis for the development of Islamic sciences. Therefore, the researcher formulated questions about the meaning and the nature of philosophy as the mother of Islamic sciences from al-Ghazali's perspectivei. This study uses philosophy as the method, and its character is rational, critical, reflective, and argumentative. Al-Ghazali's books on philosophy and logic are the data sources analyzed through the discourse analysis method. It shows that al-Ghazali criticized philosophy—as a product of thought—by using philosophy—in the sense of process—as the tool. This study found the essence of philosophy is a process that plays a role in criticizing beliefs (naqd al-i'tiqad). Philosophers do physical reflection (tabi'iyyah), mathematical reflection (riyadah), and metaphysical reflection (ilahiyyah) that produce three-level abstraction. At the highest level, the result of Kalam is an abstraction toward a pure metaphysical realm. Philosophy is just an abstraction of natural and social reality, which is not purely metaphysical. Al-Ghazali did not reduce philosophy to Kalam but placed it as the mother of the rational sciences, besides kalam that has its realm, namely pure metaphysical reality. Finally, Kalam led to the discovery of the basic assumptions of sciences, theoretical frameworks, and paradigms that are the foundation of Islamic sciences. This research concludes that the meaning of Kalam as a foundation (mabadi) is the mother of Islamic sciences, because Kalam played a role in forming basic assumptions, paradigms, and theoretical frameworks of Islamic sciences.